Mapping the interview transcript: Identifying spatial policy areas from daily working practices. Issue 4 (24th November 2017) - Orford, Scott; Webb, Brian
Abstract : An interview transcript can be a rich source of geographical references whose potential are not always fully realised in their conventional analysis. Geo‐referencing techniques can be used to assign a spatial footprint to place names, adding value to these data and allowing the geographic information within them to be exploited when coupled with GIS technology. This paper discusses a method of analysing and visualising interview transcripts in order to understand the spatial extent of public policy practitioners' activities. Through aggregation and statistical mapping it is possible to gain insight into the importance of space across a range of public policy themes and to understand the relationship between practitioner‐defined policy themes and the formal administrative boundaries within which they typically work. The research demonstrates that spatial working practices rarely conform to formal administrative boundaries and that there are varying degrees of spatial focus between different policy themes within localities. It also reveals that spatial working practices can continue to be influenced by historic geographies and can be pulled in different directions, reflecting both the devolved nature of the sector and the particular geographical context of the setting. It concludes that mapping the interview transcript can add value and provide additional insights to more conventional analysis.